Children’s Right to Privacy in the Virtual World of Apps - Kraljić, Suzana; Turnšek, Ema (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
The world has become increasingly globalized, with the exchange of goods and services spanning continents, often leading to clashes between differently regulated legal systems. A prominent example of such a conflict arises in the context of digital health applications and the processing of personal data within them. Although in the sense of human rights, the rights to privacy and data protection are guaranteed to every person with numerous national and international legal acts, and secondary law and sectoral legislation that delves into this field. In Europe, personal health data are mainly regulated with GDPR, whereas in US the field is fragmented and regulated by sectoral regulations. The issue occurs when we deal with the protection of personal health data in the virtual world of health apps, which in the US remains in the grey zone without proper legal safeguards. US HIPAA, which governs personal health data at the federal level, does not protect all data provided to a health app, not even data provided to unlicensed counsel offering services through it.